2010
DOI: 10.1603/ec09284
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance Profiles and Synergism in Field Populations of the German Cockroach (Dictyoptera: Blattellidae) From Singapore

Abstract: The resistance profiles of 22 field-collected populations of the German cockroach, Blattella germanica (L.) (Dictyoptera: Blattellidae), from various localities in Singapore were determined by topical bioassay against novel and conventional insecticides from six classes: (1) pyrethroid (beta-cyfluthrin, deltamethrin), (2) carbamate (propoxur), (3) organophosphate (chlorpyrifos), (4) phenyl pyrazole (fipronil), (5) neonicotinoid (imidacloprid), and (6) oxadiazine (indoxacarb). Compared with a laboratory suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 71 publications
6
39
0
10
Order By: Relevance
“…Our findings are consistent with other studies showing significant indoxacarb (Gondhalekar et al 2013, Ko et al 2016a) and fipronil (Holbrook et al 2003, Chai and Lee 2010, Gondhalekar et al 2011) resistance in German cockroaches. Resistance to indoxacarb and fipronil in the I-IN and D-IL strains are likely the result of prior selection pressure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with other studies showing significant indoxacarb (Gondhalekar et al 2013, Ko et al 2016a) and fipronil (Holbrook et al 2003, Chai and Lee 2010, Gondhalekar et al 2011) resistance in German cockroaches. Resistance to indoxacarb and fipronil in the I-IN and D-IL strains are likely the result of prior selection pressure.…”
Section: Discussionsupporting
confidence: 93%
“…In the case of imidacloprid, similar results were obtained in vial and no-choice feeding bioassays with gel bait. For technical imidacloprid assays, mortality was not different between the lab and field strains, which is a similar result to that obtained previously (Chai and Lee 2010). However, with technical imidacloprid 100% mortality could not be achieved, suggesting the potential for reduced imidacloprid efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Australia, resistance to cyfluthrin has been reported in Oryzaephilus surinamensis and Tribolium castaneum using filter paper and grain assays. Resistance to cyfluthrin was also reported in other insect species such as the housefly, Musca domestica L.; German cockroach, Blattella germanica (L.); beet armyworm, Spodoptera exigua (Hübner), and lesser meal worm, Alphitobius diaperinus (Panzer) . In the present study, Rhyzopertha dominica showed reduced susceptibility to chlorpyrifos‐methyl plus deltamethrin.…”
Section: Discussionsupporting
confidence: 81%
“…It is proposed that indoxacarb is effective in controlling insects that have developed resistance to carbamates, organophosphates and pyrethroids 26. A recent study by Chai and Lee27 showed that German cockroach field populations from Singapore that were resistant to organophosphates, carbamates, pyrethroids and fipronil were susceptible to indoxacarb. In another study, indoxacarb gel bait treatments were reported to be effective in eliminating German cockroach infestations in a residential area where sprays of pyrethroids, insect growth regulators and other bait formulations had proven unsuccessful 11.…”
Section: Introductionmentioning
confidence: 99%